The Influence of the Game-Based Learning Model with Baamboozle Application Media on Critical Thinking and PPKn Learning Outcomes for 2nd Grade Elementary School Students - Safitri, Dian Indah; Sumardi (Future Science, 2024)
This ponder points to decide the impact of the game-based learning demonstrate with the baamboozle application media on basic considering and civics learning results for moment review rudimentary school understudies. This inquire about could be a sort of test investigate with a quantitative approach. The method utilized is the test strategy within the shape of a quasy test plan with a pretest-posttest control gather plan. The test in this consider were understudies of SD Negeri Tempursari 01, Course II. Information collection strategies incorporate perception and tests. The information examination strategy utilized in this investigate is the test/T-test information examination procedure, where the collected information will be prepared and analyzed utilizing the typicality test and homogeneity test. The information investigation strategy utilized the SPSS form 21 application. After testing, it is known that the importance esteem is 0.000 which is underneath the foreordained importance esteem, specifically 0,000 ≤ 0,05. The comes about appeared that learning utilizing the game-based learning demonstrate with the baamboozle application media significantly impacted basic considering and learning results of PPKn understudies in lesson II character at SD Negeri Tempursari 01.